Removal of Pb(II) from aqueous solution using sawdust colonised by Pleurotus Ostreatus fungal mycelium in packed bed column / Nor Hazairianty Abdul Razak - Abdul Razak, Nor Hazairianty (2010)
The potential of sawdust colonised by Pleurotus ostreatus fungal mycelium as biosorbent in Pb(II) removal using packed bed column was investigated. This study focused on effect of flowrate to determine the efficiency of sawdust colonised by Pleurotus ostreatus fungal mycelium in removing Pb(lI) from aqueous solution. The flowrates chosen were 2, 5, 7, 10 and l4mL/min at fixed bed height of 100 mm and 50 mg/L Pb(II) concentration. As the flowrate increased, the breakthrough curve shift towards the origin, the break point time, removal efficiency and the uptake capacity of Pb(II) decreased, due to an insufficient residence time of the solution in the column. The optimum percentage removal was obtained at 88.6% and the uptake was 27.12 mg/g with the flowrate of 2 mL/min. Thomas, Adams-Bohart and Yoon-Nelson models were applied to the experimental data to establish the breakthrough curves using linear regression and to determine the characteristic parameters of the column. Experimental results fitted well to Adam-Bohart model. Application of sawdust colonised by Pleurotus ostreatus fungal mycelium in industrial electroplating wastewater indicated that it is highly potential as a biosorbent for biosorption of heavy metals. To date this represents the only report on the potential of Pleurotus ostreatus fungal mycelium in removing heavy metals under packed bed column.